2008
DOI: 10.1196/annals.1438.006
|View full text |Cite
|
Sign up to set email alerts
|

Viviparity‐driven Conflict

Abstract: Equipped with Mendel's laws and only rudimentary knowledge of genes and genomes, the architects of the Modern Synthesis provided key insights into the dynamics of gene frequency change within populations. Extension of population genetic models to speciation identified Dobzhansky-Muller incompatibilities (negative epistatic interactions between genes from isolated populations) as the primary cause of hybrid inviability and sterility, a view consistent with empirical findings on the genetics of reproductive isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 190 publications
0
15
0
Order By: Relevance
“…It has been suggested that hybrid incompatibilities in mammals develop at a much faster rate than in birds [78], possibly due to higher rates of regulatory evolution [78,79]. If reproductive isolation in mammals is determined to a greater degree by adaptive divergence at regulatory and developmental loci (such as those loci associated with placentation, genomic imprinting or mediating viviparity driven conflicts [80-82]), then the molecular change accompanying speciation may be predominantly in a few key loci, rather than due to the accumulation of genome-wide incompatibilities.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that hybrid incompatibilities in mammals develop at a much faster rate than in birds [78], possibly due to higher rates of regulatory evolution [78,79]. If reproductive isolation in mammals is determined to a greater degree by adaptive divergence at regulatory and developmental loci (such as those loci associated with placentation, genomic imprinting or mediating viviparity driven conflicts [80-82]), then the molecular change accompanying speciation may be predominantly in a few key loci, rather than due to the accumulation of genome-wide incompatibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple paternity is predicted to promote the evolution of more aggressive paternal genomes (Zeh and Zeh 2000), and since viviparity-driven conflict is predicted to be most intense where genomic-imprinting is most effective (Zeh and Zeh 2008), we may expect a more rapid evolution of postzygotic reproductive barriers in species with more invasive interhemal barriers and particularly high rates of speciation in lineages combining invasive placentation with social systems that allow for multiple paternity. While social organization was not directly tested in this study, the positive association between haemochorial placentation and large group size in our data may be indicative of the effect of social behavior, and polyandry in particular, on the importance of genomic-imprinting in a species.…”
Section: Viviparity-driven and Maternal-fetal Conflictsmentioning
confidence: 98%
“…Recently, various reviews and theoretical works have been published which propose a basic hypothesis: Drastic environmental change can disrupt the mechanism of transposon silencing and induce an explosion of transposon activity with the creation of genetic variability. The consequent burst of transpositions could help macroevolutionary processes (Zeh et al 2008; Oliver and Greene 2009; Oliver and Greene 2011; Rebollo et al 2010). This hypothesis, however, has its problems: What little experimental evidence that there is so far shows that, in organisms under stress, there is no direct correlation between the increase in transposon transcripts and the rate of transposition.…”
Section: Environmental Stress and Transposon Activitymentioning
confidence: 99%